Intensity-modulated radiotherapy for paranasal sinuses and base of skull tumors. (November 2018) - Liang, Zhong-Guo; Kusumawidjaja, Grace; Kazmi, Farasat; Wee, Joseph T.S.; Chua, Melvin L.K.
Highlights: Radiotherapy is indicated in a majority of paranasal sinus and skull base tumors. Main advantage of IMRT is in reduction of late ocular toxicities. Charged particle therapy may have better tumor control in some histologic subtypes. Abstract: Paranasal sinus and skull base tumors are rare aggressive head and neck cancers, and typically present in the locally advanced stages. As a result, achieving wide surgical resection with clear margins is a challenge for these tumors, and radiotherapy is thus usually indicated as an adjuvant modality following surgery to optimize local control. Given the integral role of radiotherapy in the management of this subgroup of head and neck tumors, the advent of intensity-modulated radiotherapy (IMRT) has led to substantial improvement of clinical outcomes for these patients. This is primarily driven by the improvement in radiation dosimetry with IMRT compared to conventional two dimensional (2D)- and 3D-techniques, in terms of ensuring dose intensity to the tumor target coupled with minimizing dose exposure to critical organs. Consequently, the evident clinical benefits of IMRT have been in reduction of normal tissue toxicities, ranging from critical neurological symptoms to less debilitating but bothersome symptoms of eye infections and radiation-induced skin changes. Another domain where IMRT has potential clinical utility is in the management of a subset of non-resectable T4 paranasal sinus and skull base tumors. For these inoperable lesions, the steep dose-gradient between tumor and normal tissue is even more advantageous, given the crucial need to maintain dose intensity to the tumor. Innovative strategies in this space also include the use of induction chemotherapy for patient selection. In this review, we summarized the data for the aforementioned topics, including specific discussions on the different histologic subtypes of paranasal sinus and skull base tumors.